How to write a thesis - Eco, Umberto (The MIT Press, 2015)
"Eco's approach is anything but dry and academic. He not only offers practical advice but also considers larger questions about the value of the thesis-writing exercise. How to Write a Thesis is unlike any other writing manual. It reads like a novel. It is opinionated. It is frequently irreverent, sometimes polemical, and often hilarious. Eco advises students how to avoid "thesis neurosis" and he answers the important question "Must You Read Books?" He reminds students "You are not Proust" and "Write everything that comes into your head, but only in the first draft." Of course, there was no Internet in 1977, but Eco's index card research system offers important lessons about critical thinking and information curating for students of today who may be burdened by Big Data." -- Publisher's description